In-patient’s satisfaction in the medical and surgical wards - A comparison between accreditted and non accreditated hospital in the state of Selangor - I Nor Hayati,; Azimatun N A,; Rozita H,; W.A Sh Ezat,; A. M R, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Background : Two of the most common indicators of institutional healthcare quality are Hospital Accreditation Status and Patient Satisfaction. However, the relationship between them is not well understood. In Malaysia, only 20.48% hospitals have been accredited. This is very much less compared to hospitals in America, Europe, Australia and certain Asian countries whereby 90% of their hospitals have already been accredited. Objective : The objective of this study was to compare the extent to which a patient’s satisfaction is related to hospital accreditation status, to examine the relationship between patient satisfaction and hospital work load and to determine factors that influence patients’ satisfaction. Methodology : A cross-sectional study was conducted whereby 150 patients from each accredited and non-accredited hospital involved in this study group giving a total of 300 samples. `SERVQUAL’ instrument was used in this study. Patients were interviewed at 2 different times - during admission and upon discharge. Result : Results showed 34.7% patients were satisfied with services in accredited hospital and 30.6% patients were satisfied with services in non-accredited hospital. `Corporate Culture’ component showed the lowest satisfaction score among the entire dimension in both categories hospitals. Patient satisfaction was noted to be reduced with increase in hospital work load. Other factors which significantly influence patient satisfaction include level of education, employment status and patient income. There was no significant difference in patient satisfaction between accredited and non-accredited hospital in all dimension measured. Conclusion : Therefore there is no difference of patients’ satisfaction with regards to services provided by accredited and non-accredited hospitals.